Comparison of Osteoarthritis Prevalence in Elderly Women with and Without Obesity Using Body Mass Index (BMI) Calculation at MH Thamrin Cileungsi Hospital for the Period of January – December 2022 - Husna, Ihsanil; Setiawan, Dinda Aulia; Syarifuddin, Faisal; Farhan, Fanny Septiani (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: Osteoarthritis (OA) is the most common form of arthritis in society throughout the world and is the main cause of disability in older adults. This disease has a slow development time with common main complaints such as pain, swelling and deformity in the affected area. This can result in limited movement and is a major cause of disability. Women are known to be more susceptible to developing OA, while advanced age is also a risk factor for developing OA. Purposes: This research is aiming to know the prevalence of OA in elderly women with and without obesity using the BMI calculation within the period of 2022. Methods: This research using a numerical analytic observation from secondary data of medical records with cross-sectional research design. Result: The study finds from the total of 196 patients, 133(67.9%) of them were obese whereas 63 (32.1%) weren't in obese condition. Conclusion: Therefore, that there was a significant difference between the average number of elderly women with and without obesity.